2012
DOI: 10.1002/elps.201100606
|View full text |Cite
|
Sign up to set email alerts
|

Functional specific roles of Hras and Nras. A proteomic approach using knockout cell lines

Abstract: Ras small GTPases function as transducers of extracellular signals regulating cell survival, growth and differentiation. There are three major ras isoforms: H-, N- and K-Ras. To improve the understanding of H- and N-Ras protein signalling networks, we compared total proteome changes in mouse embryonic fibroblasts knock out for H-ras and/or N-ras, using proteomics tools combining 2DE, semi-quantitative image analysis, in-gel trypsin digestion and mass spectrometry. There are four up-regulated proteins due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(70 reference statements)
0
2
1
Order By: Relevance
“…How KRAS mutation drives ERCC1 downregulation remains to be understood, but recently it has been shown that in breast cancer cells the expression of ERCC1 is regulated by H-RAS, one of the three proteins of the RAS family, through AP-1 29 . Contrary to what was observed in the past, it has also been shown that the three protein of RAS family (N-RAS, KRAS and H-RAS), have different activities and each may affect the synthesis and function of the others 30 - 31 . Therefore it is conceivable that mutational status of KRAS can influence the activity of H-RAS, and consequently the expression of ERCC1.…”
Section: Discussioncontrasting
confidence: 57%
“…How KRAS mutation drives ERCC1 downregulation remains to be understood, but recently it has been shown that in breast cancer cells the expression of ERCC1 is regulated by H-RAS, one of the three proteins of the RAS family, through AP-1 29 . Contrary to what was observed in the past, it has also been shown that the three protein of RAS family (N-RAS, KRAS and H-RAS), have different activities and each may affect the synthesis and function of the others 30 - 31 . Therefore it is conceivable that mutational status of KRAS can influence the activity of H-RAS, and consequently the expression of ERCC1.…”
Section: Discussioncontrasting
confidence: 57%
“…Chloride intracellular channel proteins (CLIC), S100 proteins, tropomyosins (TPM), cathepsins, α-integrins (ITGA), eukaryotic elongation factors (EEF), and vimentin (VIM) were also discriminated through analyses on the RAS-modulated proteome of different types of cells investigated in previous studies [21][31]. The results obtained suggested that these could be important molecules participating in RAS-mediated carcinogenesis.…”
Section: Discussionmentioning
confidence: 93%
“…Dihydropyrimidinase‐related protein 3 is required for signalling by class 3 semaphorins and subsequent cytoskeleton remodelling. It is associated with neurofibromin, a negative regulator of Ras, indicating a role for DRP‐3 in proliferation and neural morphogenesis . Its regulation by retinoic acid also suggests a role in differentiation .…”
Section: Discussionmentioning
confidence: 99%